FINANCIAL INSTABILITY THEORY IN THE SCIENTIFIC TOOLS OF THE MODERN MACROECONOMICS - I. Radionova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2013)
The article under review gives prominence to the changes in the macroeconomic tools of science influenced by the theory of financial instability.